Kynurenine and Tryptophan Levels in Patients With Schizophrenia and Elevated Antigliadin Immunoglobulin G Antibodies. Issue 8 (October 2016) - Okusaga, Olaoluwa; Fuchs, Dietmar; Reeves, Gloria; Giegling, Ina; Hartmann, Annette M.; Konte, Bettina; Friedl, Marion; Groer, Maureen; Cook, Thomas B.; Stearns-Yoder, Kelly A.; Pandey, Janardan P.; Kelly, Deanna L.; et al.
ABSTRACT: Objective: Several studies have reported an association between nonceliac gluten sensitivity and schizophrenia. Immune and kynurenine (KYN) pathways have also been implicated in the pathophysiology of schizophrenia, and certain proinflammatory immune mediators may increase KYN and reduce tryptophan (TRP) levels. Methods: We measured serum antigliadin immunoglobulin G (IgG), KYN, and TRP in 950 patients with schizophrenia. Patients with antibody level at the 90th percentile or higher of control participants (21.9% of all patients) were classified as having elevated antigliadin IgG. Independent t tests and linear regression models were used to compare TRP, KYN, and KYN-TRP ratio (indicator of TRP metabolism) between patients with and those without elevated antigliadin IgG. The correlation between antigliadin IgG and TRP, KYN, and the ratio was also evaluated in the patients. Results: KYN and KYN-TRP ratio were higher in patients with elevated antigliadin IgG (geometric mean [standard deviation SD] = 2.65 [0.25] µmol/L versus 2.25 [0.23] µmol/L [ p < .001] and 0.05 [0.26] versus 0.04 [0.25; p = .001] respectively), findings robust to adjustment for potential demographic and clinical confounders. Antigliadin IgG positively correlated with KYN and KYN-TRP ratio ( r = 0.12, p < .001; r = 0.11, p = .002). TRP did not differ between the two groups and did not correlate with antigliadin IgG. Conclusions: Our results connect nonceliac gluten sensitivity with the KYN pathway of TRP metabolism in psychotic illness and hint toward potential individualized treatment targets.